Association of obesity with diabetic retinopathy in US adults with diabetes in a national survey. Issue 7 (30th June 2021) - Yang, Guang-Ran; Li, Dongmei; Xie, Zidian
Abstract : Objective: There is a lack of consensus on whether a high BMI increases the risk of diabetic retinopathy (DR). We aimed to investigate the association between BMI, overweight, obesity, and DR using the data of diabetes respondents in the 2015 US Behavioral Risk Factor Surveillance System survey. Methods: Diabetes respondents aged over 18-year-old with complete information as well as undergone fundus examination in the past 2 years or had been diagnosed with DR were included. Weighted logistic regression analyses were used to identify the association of BMI with DR. Results: Among the 21, 647 diabetes respondents, 4588 respondents had DR with a weighted prevalence of 22.5%. The mean BMI of all diabetes respondents was 31.50 ± 6.95 kg/m 2 with 18, 498 (86.5%) overweight and 11, 353 (54.6%) obese. The mean BMI of the DR group (31.83 ± 7.41 kg/m 2 ) was significantly higher than that of the non-DR group (31.41 ± 6.81 kg/m 2, P < 0.05). The proportion of obese respondents in the DR group was higher than the non-DR group (54.3%, P < 0.001). The weighted prevalence of DR was 0.8, 13.8, 29.7, and 55.7% for the emaciation group, the normal weight group, the overweight group, and the obesity group, respectively ( P < 0.001). Weighted logistic regression analysis showed that both BMI (adjusted OR = 1.004, 95% CI 1.003–1.004) and obesity (adjusted OR = 1.051, 95% CI 1.048–1.055) were associated with DR after adjusting for the confounding variables. However, overweight was not significantly associated with DR. Conclusion: The prevalence of DR in the normal weight, overweight, and obesity groups increased gradually. Obesity, rather than overweight, was significantly associated with increased DR prevalence.